Marketing Research / Seventh Edition - Luck J. David; Rubin Ronald S (Prentice Hall International, 1987)
Preface, Fundamentals, Planning the Research Project, Performing the Data Collection, Processing and Analyzing Data, Presentation and Follow-Through, Indexes.
Preface, Fundamentals, Planning the Research Project, Performing the Data Collection, Processing and Analyzing Data, Presentation and Follow-Through, Indexes.